Prognostic significance vestibular examination results in patients with vestibular migraine - Goto, Fumiyuki; Wasano, Koichiro; Kaneda, Shoji; Okami, Kenji (Frontiers in Neurology, 2024)
Introduction Vestibular migraine (VM) is a newly defined clinical condition. Several vestibular abnormalities have been reported in patients with VM. However, to date, no specific vestibular examinations are used to define VM. Therefore, the utility of vestibular examinations is limited. Currently, the role of vestibular examination has not been clearly defined. We speculated that the results of vestibular examinations could predict the prognosis of VM. We investigated the relationship between the vestibular examination results and clinical outcomes in patients with VM. Methods This study included 25 patients with VM. Vestibular examinations, including the video head impulse test (V-HIT), cervical and ocular vestibular evoked myogenic potential (c-VEMP and o-VEMP), posturography, and several questionnaires, including the Dizziness Handicap Inventory (DHI), were conducted at the initial evaluation. Lifestyle modifications for VM and conventional pharmacological prophylactic treatments, including lomerizine, amitriptyline, and valproic acid, were performed. After 4 weeks of treatment, clinical improvements were evaluated using the Clinical Global Improvement Scale (CGI-s). The relationships among the CGI-S score, several clinical variables, and the results of several vestibular examinations were evaluated. Each patient was further classified into two subgroups according to treatment outcomes concerning vertigo and headache: CGI-S score from 0 to 2 (good response [GR]) and CGI-S score > 3 (poor response [PR]). Results Overall, after treatment, most of the patients had improved dizziness and headache, and the CGI-s was 2.7 ± 1.3. There were 12 GRs, and 13 had PRs. Thus, neither V-HIT nor posturography predicted the prognosis. For c-VEMP, patients with GRs had significantly small AR concerning PR (19.2 ± 12.8 and 62.5 ± 42.5, respectively, [p < 0.01]). There were five normal, six unilateral, and 14 bilateral no response in 500hz o-VEMP. CGI-s of normal, unilateral, and bilateral no response was 1.4 ± 0.5, 2.8 ± 1.3, and 3.1 ± 1.2, respectively. There was a statistically significant difference between the normal and bilateral non-response o-VEMP groups (p < 0.05). Conclusion Patients with VM had improvements in both headache and vertigo through a combination of lifestyle changes and prophylactic medications. Vestibular examinations, especially o- or c-VEMP, are beneficial for predicting the treatment outcomes of VM. The pathophysiology of VM is closely related to vestibular abnormalities, particularly the otolith-related pathways.